Practice Education in Wales: progress and limitations - Mohammed, Imran (The Journal of Practice Teaching and Learning, 2022)
In this paper I discuss the role of the Practice Educator and the need for further exploration of research in Wales. I explain in this paper that there is a 'role' conflict between practice assessor and 'educator'. The literature that is currently available on Practice Education includes the perspectives of Practice Educators in England. I therefore argue that a 'body of knowledge' is required to better understand the role of the Practice Educator in Wales.